2019
DOI: 10.1177/2050312119857353
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug–drug interactions and associated factors among hospitalized cardiac patients at Jimma University Medical Center, Southwest Ethiopia

Abstract: Background: Concomitant use of several drugs for a patient is often imposing increased risk of drug–drug interactions. Drug–drug interactions are a major cause for concern in patients with cardiovascular disorders due to multiple co-existing conditions and the wide class of drugs they receive. This study is aimed to assess the prevalence of potential drug–drug interactions and associated factors among hospitalized cardiac patients at medical wards of Jimma University Medical Center, Southwest Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 35 publications
9
50
4
4
Order By: Relevance
“…Similarly, this review showed all (100%) HIV infected patients treated in the outpatient setting [6]97.5% of adult patients with heart diseases treated in inpatient ward [5] and 92.23% cardiac disorder patients treated in the outpatient setting [26] were susceptible to DDIs. A high number of prescribed drugs, prescribing drugs with many potential DDIs, pharmacodynamics nature of drugs used in cardiology, and the in uence of heart disease on drug metabolism may cause the high occurrence of potential DDIs in this group of patients.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Similarly, this review showed all (100%) HIV infected patients treated in the outpatient setting [6]97.5% of adult patients with heart diseases treated in inpatient ward [5] and 92.23% cardiac disorder patients treated in the outpatient setting [26] were susceptible to DDIs. A high number of prescribed drugs, prescribing drugs with many potential DDIs, pharmacodynamics nature of drugs used in cardiology, and the in uence of heart disease on drug metabolism may cause the high occurrence of potential DDIs in this group of patients.…”
Section: Discussionmentioning
confidence: 94%
“…WA also prepared the manuscript for publication. All authors have read and approved the manuscript Footnote: Seven studies did not report the mechanisms of drug-drug interaction Patients taking three or more than three concomitant drugs are at higher risk of the occurrence of potential DDIs [27,28] There is an association of the occurrence of one or more potential DDIs with the number of medications prescribed per patient who took more than four medications [35] Polypharmacy(five or more medications) is an important factor which leads to potential DDIs [5,29,30,31,33,34] Co-morbid disease Co-morbid condition independently increased the potential DDIs almost 2-folds [33] Age Older age was found to be predisposing factors for the occurrence of DDI [5,28,30,31] Potential DDIs were occurring more frequently in the age group of 2-6 years than any other age group of the pediatric population [29] Hospital stay The chance of taking multiple drugs increases with longer stays(greater than or equal to seven) in the hospital, which in turn increases the risk for potential DDIs [5] International Normalized ratio (INR value) Increase in international normalized ratio value was found to be strongly associated with DDI and hence the risk of bleeding [32] Footnote: Ten studies did not report the mechanisms of drug-drug interaction Forest plot depicting the pooled prevalence of moderate potential DDIs of 14 studies in Ethiopian Hospitals Figure 5 Forest plot depicting the pooled prevalence of minor potential DDIs of 14 studies in Ethiopian Hospitals Figure 6 Subgroup analysis of the prevalence of potential DDIs based on region…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations